Penerapan Evidence Based Practice Teknik Relaksasi Nafas dalam Upaya Menurunkan Tekanan Darah pada Penderita Hipertensi - Chairunnisa, Chairunnisa; Lontoh, Esther (Yayasan Syalom Cipta Sumikolah, 2025)
According to the 2018 National Health Research (Riskesdas) report, approximately 34.11% of the population aged ≥ 18 years old suffered from hypertension. The number of cases of hypertension in North Sulawesi reached 32,742. Nursing care provided included electrolyte fluid therapy and medication to address fluid balance and reduce pain, as well as pain management using deep breathing relaxation techniques, which can also help reduce pain. The study found that acute pain was associated with increased cerebral vascular pressure. Sleep disturbances were associated with psychological injury agents (pain, anxiety). Anxiety was associated with a lack of exposure to information about the disease process. The final result showed that headaches decreased, insomnia complaints began to improve, and feelings of anxiety and worry had decreased. Conclusions: Fluid therapy, medication, and deep breathing relaxation techniques can address pain, sleep disturbances, and anxiety. Families are advised to always maintain and monitor their health at the nearest hospital or community health center.